Beta-Alanine supplementation for 10 weeks was unable to improve training and competition performance in elite swimmers - Chung, W.; Shaw, G.; Anderson, M.; Pyne, D. B.; Saunders, P. U.; Bishop, D. J.; Burke, L. M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Although some laboratory-based studies show an ergogenic effect with beta-alanine supplementation, there is a lack of field-based research in training and competition settings. This study investigated the effects of beta-alanine supplementation on training and competition performance in international level swimmers. Methods: Elite swimmers (n = 27 males and 21 females, age = 21.7 ± 3.1 yr; mean ± SD) were supplemented with either beta-alanine (BA; 4 week loading phase of 4.8 g/day with a maintenance dose of 3.2 g/day thereafter) or placebo (PLA) for 10 weeks. Competition performance was evaluated before (National Championships; CPRE) and after (World Championships or national selection meet; CPOST) supplementation using IPS points. Swimmers also completed three standardised sessions (sprinters 4 x 50 m, 100 m; middle-distance 6 x 50 m, 200 m; distance 8 x 50 m, 200 m) in training at baseline (TPRE), 4 weeks (TMID) and 10 weeks (TPOST) of supplementation. Capillary blood was analysed for pH, bicarbonate and lactate concentration in both competition and training. We employed a contemporary analytical approach involving magnitude-based inferences to detect small effects of practical importance in an elite athlete group. Precision of estimation expressed as 90% confidence limits (CL) to evaluate differences within and between groups. Results: There was a trivial effect (-1.2 ± 2.3%; mean ± 90% confidence limits) of BA on race performance compared with PLA and no meaningful effect on blood measures (post race pH (0.2 ± 0.8%); post race bicarbonate (-6.7 ± 22.6%)). For training performance with all three groups combined, there was no substantial effect of BA at TMID and TPOST (-0.1 ± 1.2%; -0.1 ± 1.4%). There were also no meaningful effects on post training blood pH at TMID and TPOST (-0.1 ± 0.7%; 0.2 ± 0.7%) or bicarbonate (3.6 ± 13.5%; 2.7 ± 16.4%). However, post-training blood lactate concentration at TPOST was reduced by -11.0 ± 9.9%. Discussion: We were unable to demonstrate an ergogenic effect of beta alanine supplementation in elite level swimmers due to the trivial or unclear results in our study. More work is required to clarify how the results of laboratory-based studies showing positive effects of beta alanine can be transferred effectively into improved real world training and competitive performance.